THE CORRELATION AMONG METACOGNITIVE AWARENESS, EXTRINSIC MOTIVATION, AND WRITING ABILITY OF THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FACULTY OF TEACHER TRAINING AND EDUCATION OF PGRI UNIVERSITY OF PALEMBANG - Verawati Verawati (Universitas PGRI Palembang, 2019)
AbstractThis study is concerned with the inquiry on the correlation among metacognitive awareness, extrinsic motivation and writing ability. This study is aimed to investigate the empirical evidence about metacognitive awareness and extrinsic motivation and its correlation to writing ability. The population of this study encompassed all the sixth semester students ofEnglish study program of faculty of teacher training and education of PGRI university of Palembang of which total is 71 students. From the population, only 35 students were taken as the samples. The systematic non-random sampling technique was used in recruiting the samples. Data were collected through tests and questionnaire. Data were analyzed by using Pearson Product Moment and multiple regressions to find out the correlation amongmetacognitive awareness and extrinsic motivation simultaneously on writing ability. Findings showed that there was significant correlation between metacognitive awareness and writing ability, and between extrinsic motivation and writing ability. Multiple regressions indicate that there were significant correlation of metacognitive awareness and extrinsic motivationsimultaneously on writing ability. In conclusion, there is significant correlation among metacognitive awareness, extrinsic motivation and writing ability. At the same time, both metacognitive awareness, extrinsic motivation affect writing ability of the sixth semester students of english study program of faculty of teacher training and education of PGRIuniversity of Palembang.Keywords: Metacognitive Awareness, Extrinsic Motivation, Writing Ability,Correlation, Multiple Regressions.